2017
DOI: 10.1073/pnas.1707072114
|View full text |Cite
|
Sign up to set email alerts
|

Acidophilic green algal genome provides insights into adaptation to an acidic environment

Abstract: Some microalgae are adapted to extremely acidic environments in which toxic metals are present at high levels. However, little is known about how acidophilic algae evolved from their respective neutrophilic ancestors by adapting to particular acidic environments. To gain insights into this issue, we determined the draft genome sequence of the acidophilic green alga and performed comparative genome and transcriptome analyses between and its neutrophilic relative The results revealed the following features in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 81 publications
4
69
3
Order By: Relevance
“…Antenna complexes (nuclear-encoded) experienced adaptive modifications reducing light absorption efficiency and further decreasing the probability of damage to photosystem [ 58 ]. Another possible explanation is that adaptive modifications on other abiotic stresses targeting genes were sufficient to maintain the homeostasis for photosynthesis without the need of adaptive evolution of chloroplast-encoded photosynthetic subunits [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antenna complexes (nuclear-encoded) experienced adaptive modifications reducing light absorption efficiency and further decreasing the probability of damage to photosystem [ 58 ]. Another possible explanation is that adaptive modifications on other abiotic stresses targeting genes were sufficient to maintain the homeostasis for photosynthesis without the need of adaptive evolution of chloroplast-encoded photosynthetic subunits [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…other than C. reinhardtii are adapted to a wide range of habitats. For example, Chlamydomonas eustigma is an acidophilic species isolated from acid mine drainage ( Hirooka et al, 2017 ), Chlamydomonas euryale is found in temperate marine environments ( Burch et al, 2015 ), Chlamydomonas spp. have been isolated from Antarctic ice ( Liu et al, 2006 ), and some members of the genus Chlamydomonas are carotenoid-rich organisms present on the surface of snow, giving it a red appearance ( Remias et al, 2005 ).…”
Section: Habitats and Biogeographymentioning
confidence: 99%
“…Likewise, genome sequencing and transcriptomics studies are beginning to identify the array of genes that might explain extremophile functional characteristics, some of which may have been obtained by horizontal gene transfer from bacteria. Genome sequences of the acidophiles Chlamydomonas eustigma (Hirooka et al, 2017) and Galdieria sulphuraria (Schönknecht et al, 2013) have recently been determined. Furthermore, transcriptomic approaches are beginning to provide insight into the molecular mechanisms of Chlamydomonas acidophila tolerance in response to Cd and Cu exposure (Olsson et al, 2015;Puente-Sánchez et al, 2018), and Dunaliella acidophila in response to Cd (Olsson et al, 2017;Puente-Sánchez et al, 2016), although further experimental analyses of these transcriptomic datasets are needed.…”
Section: Introductionmentioning
confidence: 99%